2013
DOI: 10.2174/1874328501307010104
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Optical Fiber Sensing Based on Rayleigh Scattering

Abstract: Optical fiber sensors offer unprecedented features, the most unique of which is the ability of monitoring variations of the observed physical field with spatial continuity along the fiber. These distributed optical fiber sensors are based on the scattering processes that originate from the interaction between light and matter. Among the three different scattering processes that may take place in a fiber—namely Rayleigh, Raman and Brillouin scattering, this paper focuses on Rayleigh-based distributed optical fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(104 citation statements)
references
References 213 publications
2
100
0
2
Order By: Relevance
“…This round-trip pulse travel time light multiplied by the speed of light in the FUT, is used to calculate the round-trip distance. The distance from the OTDR to the measured point is the half of the round-trip distance (Palmieri and Schenato 2013). Finally, distance-attenuation graphics are obtained as shown in Fig.…”
Section: Optical Time Domain Reflectometer (Otdr)mentioning
confidence: 99%
“…This round-trip pulse travel time light multiplied by the speed of light in the FUT, is used to calculate the round-trip distance. The distance from the OTDR to the measured point is the half of the round-trip distance (Palmieri and Schenato 2013). Finally, distance-attenuation graphics are obtained as shown in Fig.…”
Section: Optical Time Domain Reflectometer (Otdr)mentioning
confidence: 99%
“…Brillouin systems can achieve spatial resolution down to ~1 cm, while Raman is limited to ~1 m; time response is generally on the order of minutes (Bao and Chen 2012) though some commercial systems can now achieve data rates of approximately 1 Hz. Comprehensive reviews of the physics of fiber optic sensors can be found in (Bao and Chen 2012;Palmieri and Schenato 2013).…”
Section: Sensing With Scattered Lightmentioning
confidence: 99%
“…Reflectometer) systems have already been demonstrated for distributed long-distance sensing [2,7]. However, there are barriers to achieving dynamic performance using these systems, such as the need to sweep through a large overall frequency span to find the Brillouin frequency shift (or Rayleigh equivalent in the COTDR system); the need for ensemble averaging to increase the Signal-to-Noise Ratio (SNR); and the time taken for the pulse to transit the fibre (in very longdistance sensing) [8].…”
Section: Botda (Brillouin Optical Time Domain Analysis) and Cotdr (Comentioning
confidence: 99%